Values in Board Games: conscientious design as an alternative to the colonial hegemony of the industry - Monfort, Pedro Podboy; Nesteriuk Gallo, Sérgio (DAT Journal, 2024)
This study analyzes the work of Flannagan and Nissenbaum (2016) on values in games, with the aim of recognizing the process of production of meaning in design and, through a comparative analysis, creating a relationship with the historical research on the theme of colonization in board games present in the books of Torner, Waldron and Trammell (2016, 2017 and 2019). Through this relation, we seek to highlight the problems in this industry – originating from a colonial thinking inherited from Europe in the 20th century, more specifically from Germany in the post-war period. In a proactive manner, we identify ways in which conscientious design can be used as a tool to avoid the repetition of hegemonic tropes, propose thematic and formal innovations in the field of boardgame design.